Group counseling to reduce academic stress in senior high school students - Katrim Alifa Putrikita; Endah Puspita Sari (Konselor, 2020)
The objective of the study is to determine the effect of group counseling on academic stress of senior high school students. Academic stress is a student's response to academic demands that cannot be prevented, avoided or controlled. Respondents in this study were four senior high school students who had high academic stress scores. This study used a quasi-experimental one-group pretest-posttest design. Researchers measured respondents' academic scores before and after the group counseling was given. Researchers used the Educational Stress Scale for Adolescents (ESSA) to measure the academic stress of respondents. The treatment given, which was group counseling, was given in five sessions. Researchers used anava repeated measures to analyze the data. From the statistical analysis conducted, it can be concluded that group counseling has a significant effect on reducing the academic stress of the research respondents. From the results of this study, researchers suggest that group counseling is effective for reducing academic stress in senior high school students.